The afferent connections of the posterior hypothalamic nucleus in the rat using horseradish peroxidase - ONAT, FİLİZ; YANANLI, HASAN RACİ; GÜLHAN, REZZAN (WILEY, 2001)
The posterior hypothalamic nucleus has been implicated as an area controlling autonomic activity. The afferent input to the nucleus will provide evidence as to its role in autonomic function. in the present study, we aimed to identify the detailed anatomical projections to the posterior hypothalamic nucleus from cortical, subcortical and brainstem structures, using the horseradish peroxidase (HRP) retrograde axonal transport technique in the rat, Subsequent to the injection of HRP into the posterior hypothalamic nucleus, extensive cell labelling was observed bilaterally in various areas of the cerebral cortex including the cingulate, frontal, parietal and insular cortices. At subcortical levels: labelled cells were observed in the medial and lateral septal nuclei, the bed nucleus of stria terminalis, and various thalamic and amygdaloid nuclei. Also axons of the vertical and horizontal limbs of the diagonal band were labelled and labelled cells were localised at the CA1 and CA3 fields of the hippocampus and the dentate gyrus. The brainstem projections were from the medial, lateral and parasolitary nuclei, the intercalated nucleus of the medulla, the sensory nuclei of the trigeminal nerve, and various reticular, vestibular, raphe and central rey nuclei. The posterior hypothalamic nucleus also received projections from the lateral and medial cerebellar nuclei and from upper cervical spinal levels. The results are discussed in relation to the involvement of the posterior hypothalamic nucleus in autonomic function and allows a better understanding of how the brain controls visceral function.
Keywords: hypothalamus; autonomic function; INSULAR CORTEX; PARABRACHIAL NUCLEUS; MACACA-FASCICULARIS; DEFENSE REACTION; CEREBELLAR; NEURONS; BRAIN; RESPONSES; PATHWAYS; AREA